Mesoporous, hierarchical core/shell structured ZnCo2O4/MnO2 nanocone forests for high-performance supercapacitors. (January 2015) - Qiu, Kangwen; Lu, Yang; Zhang, Deyang; Cheng, Jinbing; Yan, Hailong; Xu, Jinyou; Liu, Xianming; Kim, Jang-Kyo; Luo, Yongsong
Abstract: ZnCo2 O4 /MnO2 nanocone forests with a mesoporous, hierarchical core-shell structure and a large surface area were hydrothermally grown on 3D nickel foam. The supercapacitor electrodes prepared from the unique structure exhibits exceptional specific capacitances of 2339 and 1526 F g −1 at current densities of 1 and 10 A g −1, respectively, and long-term capacity retention of ~95.9% after 3000 cycles at 2 A g −1 and 94.5% after 8000 cycles at 10 A g −1 . These values are proven to be the highest when the capacitances are compared between the current study and similar core/shell-structured metal oxide electrodes taken from the literature. Many synergistic effects are identified to be responsible for the observations: namely, highly conductive 3D Ni foam substrate that totally eliminate binders and conductive additives; high crystalline quality of the ZnCo2 O4 core which is directly grown on the conductive current collector, allowing fast electron transport; and the mesoporous MnO2 shell with a huge surface area for fast ion diffusion and intimate electrode/electrolyte contact. In addition, the nanostructured core and shell have redox reactions with anions and cations from the electrolyte, respectively, both of which contribute much to electrochemical charge storage. Graphical abstract: Hierarchical ZnCo2 O4 @MnO2 core-shell nanowire arrays on porous Nickel Foam substrate are synthesized through a simple hydrothermal approach and further investigated as the electrode materials for supercapacitors. Highlights: We firstly report the mesoporous ZnCo2 O4 /MnO2 composite nanocone forests. ZnCo2 O4 /MnO2 nanocones are fabricated by a facile hydrothermal approach. This core/shell structure shows the fascinating synergetic properties. The application as a binder-free electrode for high-performance supercapacitors. ZnCo2 O4 /MnO2 nanocones show superior electrochemical performance.